La sociologie de l’ignorance de Amos Funkenstein et Adin Steinsaltz - Ilana Löwy (Revue d'anthropologie des connaissances)
This article introduces and contextualized an essay, Sociology of Ignorance, written by two well-known historians of ideas, Amos Funkenstein and Adin Steinsaltz. This study explains that the concept of “open science”, accessible to all, was born, independently, in two cultural traditions: the Hebrew one, with development of studies of religious texts grounded in collective debates, and the Greek one, with the development of mathematic proof. Diffusion of “open science” was accompanied by a parallel diffusion of ignorance. Production of knowledge and ignorance are related but distinct domains. Ignorance is not defined as a mere absence of knowledge, but as a distinct entity, actively produced and maintained through specific and powerful mechanisms, such as the occultation of information, its devalorization, and deliberate disinformation.